THE DIGITALIZATION AND SMART SPECIALIZATION IN REGIONAL ECONOMIC ECOSYSTEMS: INTEGRATING AI TECHNOLOGIES FOR SUSTAINABLE DEVELOPMENT - Mykolaichuk, Mykola; Kusplіak Ihor (Public Management and Policy, 2025)
The article examines digitalization and smart specialization as complementary mechanisms for transforming Ukraine’s regional economic ecosystems under technological instability and martial law. Smart specialization is considered “architectonics” of economic interaction, where local resources gain new significance through alignment with human capital, entrepreneurship, and technology, generating long-term structural development impulses. Institutional trust serves as a key channel for communication and innovation. Digitalization is not merely the digitization of services but a foundation for integration processes that create a new socio-economic experience and redefine the roles of government, business, and communities. The concept of digital ecology encompasses coordination of information flows, interaction speed, and accumulation of local knowledge, reducing developmental entropy and enabling controlled scenarios. Analysis of the legal framework for smart specialization shows that its effectiveness depends on alignment with informal practices, local initiative, and risk readiness. Under these conditions, a new type of collective entrepreneurship emerges, creating not only market niches but also communicative bridges between local and global spaces. Integration of artificial intelligence in regional governance enables early detection of systemic weaknesses and optimization of resources through predictive models and policy evaluation algorithms. The dynamics of the Regional Digitalization Index in Q1–Q2 2025 demonstrate uneven adaptation, reflecting local developmental specificity. During wartime, digitalization acts as a mechanism of social solidarity, supporting remote employment, internally displaced persons, and adaptation of services to limited resources. The symbiosis of digitalization and smart specialization creates adaptive and technologically resilient economic systems, where digitalization ensures rapid response and smart specialization ensures sensitivity to opportunities. This enables regions to overcome exogenous shocks and integrate into global innovation chains.